2022
DOI: 10.1097/qai.0000000000003090
|View full text |Cite
|
Sign up to set email alerts
|

High Unreported Mortality in Children and Youth (<25 Years) Living With HIV Who Were Lost to Care From Antiretroviral Therapy Programs in Southern Africa: Results From a Multicountry Tracing Study

Abstract: Background: Antiretroviral therapy program mortality maybe underestimated if deceased patients are misclassified as lost. Methods:We used two-stage inverse probability weighting to account for probability of being: sampled for tracing and found by the tracer.Results: Among 680 children and youth aged ,25 years on antiretroviral therapy who were lost and traced in Southern Africa between October 2017 and November 2019, estimated mortality was high at 9.1% (62/680). After adjusting for measured covariates and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Our study confirms previous findings that reported LTFU is non-ignorable, as patients reported as lost were identified as deceased or self-transferred, and demonstrates the complementarity of tracing and linkage in outcome ascertainment [9,17,[24][25][26]. In addition, the reasons for reported LTFU among CAYHIV may be different from those of adults.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study confirms previous findings that reported LTFU is non-ignorable, as patients reported as lost were identified as deceased or self-transferred, and demonstrates the complementarity of tracing and linkage in outcome ascertainment [9,17,[24][25][26]. In addition, the reasons for reported LTFU among CAYHIV may be different from those of adults.…”
Section: Discussionsupporting
confidence: 87%
“…Although mortality was higher among CAYHIV reported as LTFU and traced compared with those retained [16, 17, 25–28], previous studies have reported even higher mortality estimates in those LTFU [1, 3, 29]. In rural Tanzania, 40% of adults living with HIV who were reported LTFU and traced, had died [27].…”
Section: Discussionmentioning
confidence: 99%
“…This number likely includes a substantial number who remained in care but transferred out of the respective cohort, especially within VICONEL, which does not have a system to capture transfers to non-VICONEL clinics. Nevertheless, children and adolescents with HIV with missing viral loads might have higher rates of viraemia and subsequent poor outcomes, as described in a multinational tracing study [ 32 ] for the predolutegravir era. Second, there may be unmeasured confounders.…”
Section: Discussionmentioning
confidence: 99%
“…We observed far lower mortality compared to children who were traced in Malawi (2.6% vs. 11%) and 6 southern African countries (2.6% vs. 9%). 22,23 Mortality may be lower in the WC than in Malawi or other southern African countries due to better access to health care, nutrition and less poverty. 2,[24][25][26] Conversely, our study may have underestimated mortality because of limited death ascertainment outside the WC.…”
Section: Discussionmentioning
confidence: 99%